Special Interest Groups 2005 : Faculty of Information Management / Universiti Teknologi MARA - UiTM, Faculty of Information Management (Universiti Teknologi MARA, 2005)
The book - Special Interest Groups (SIG), Faculty of Information Management, is designed to assist the public at large in their search for Malaysian expertise and experts to carry out various tasks relating to the many facets of managing information in whatever formats, whichever situations, regardless of types of organizations. In the current world scenario where "Information Is Power", the powerful ones are those who know how and where to search for information, to organize, manage, retrieve, evaluate and use that which is relevant in certain situations, for particular purposes. Hence the art and science of information management, record management, and library management have continue to grow as much as the rapid growth of information itself. The need continues to increase for services of information professionals to carry out the necessary tasks for organizations that value and wish to harness the power of information and transform it into competitive advantage. Throughout the years, the Faculty of Information Management has built up its strength in research and consultancy in the above fields to be of service to the public. This Special Interest Groups (SIG) is the faculty attempt to officially document the tacit knowledge and transform it into explicit knowledge, mirroring our desire to share our knowledge for the benefits of the community at large.